The Pengaruh Model Pembelajara Talking stick Terhadap Kemampuan Mengidentifikasi Isi Teks Deskripsi Siswa Kelas VII SMP Negeri 40 Batam Tahun Pelajaran 2023/2024 - Isnaini Leo Shanty; Tetty Kurmalasari; Dody Irawan; Harry Andheska; Legi Elfitra; RIQQAH RAHMADIA ISMAIL (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to describe the influence of the talking stick learning model on the ability to identify the content of descriptive text in class VIII of Batam 40 State Junior High School for the 2023/2024 academic year. The method used in this research is a quantitative descriptive method. Normality test provisions use the Kolmogrov-Smirnov formula. Judging from the significance of the pretest data, it is 0.001 < 0.05, so the data is not normally distributed. In the posttest results, the data had an abnormal distribution with a significance of 0.001 < 0.05. It was concluded that the data was not normally distributed, so non-parametric tests were used for hypothesis testing. After carrying out normality and homogeneity tests to see whether the data was influential or not, the researcher carried out a hypothesis test using the Wilcoxon test to obtain Asymp.Sig. (2-tailed) amounts to 0.001. The test decision value is 0.001 < 0.05, then Ha is accepted and Ho is rejected. The conclusion of the research is that there is an influence of the talking stick model on the ability to identify the content of descriptive text of class VII students at State Junior High School 40 Batam for the 2023/2024 academic year. Based on the explanation above, it is concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The talking stick learning model can have an influence on increasing the ability to identify the content of descriptive text for class VII students.